Efektivitas Metode Kelompok terhadap Peningkatan Pengetahuan Wanita Tani dalam Pemanfaatan Lahan Pekarangan di Desa Kalimas Kecamatan Kaledupa Kabupaten Wakatobi - Ningsih, Novia; Nalefo, La; Wunawarsih, Ima Astuty (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
The Purpose of This Study Was to Examine The Effectiveness of Public Meeting Compared with a Demonstration Plot Toward Farmers Women as User of Yard Area in Kalimas Village of Kaledupa Sub-district of Wakatobi Regency. The technique of Sampling was used Random Sampling Method. In this Study was Observed Group Method Which Consists of Two Type of Group Method Like Public Meeting Methods and Demonstration Plot, and Farmers Woman Knowledge to Measure the Respondents Scores Achievement on Material Presented with Public Meeting Method and Demonstration Plot in Utilization of Yard Area. The Data was Tabulated, Presented and Analyzed Used Descriptif Kuantitatif. The Result of this Study Showed that Demonstration Plot was more Effective with Value of Presentation 58,68% in Increase Farmers Woman Knowledge in Utilization of Land Yard Area, Than Public Meeting Method with Value of Percentage 48,17% Toward Farmers Woman Respondents.